Title-Exchange (2021)
Facilitate the exchange of digital video games, which is free and builds trust. According to a report from the newspaper El Tiempo, 48% of the software in Colombia is illegal (pirated), although the outlook is not good, at least the country is better located with reference to Venezuela, which has 89%. In the video game industry, it is not strange to talk about piracy openly, as was mentioned in the problem, the cost of an original video game is high, that is why many Gamers incur in piracy or the exchange of a video game, but with this the best solution is that we can make an exchange keeping the original game that belongs to us.